Peran Rasa Syukur dalam Pengendalian Kecemasan dan Stress pada Mahasiswa - Haq, Aniq Hudiyah Bil; Nulipata, Muslimin; Ramdani , Aulia; Damayanti, Desita Dyah; Suen, Mein-Woei; Hamka, Hamka; Haq, Alfiza Fakhriya (Universitas Muhammadiyah Yogyakarta, 2025)
Anxiety and stress can have a psychological effect on the student learning process. Students need to reduce anxiety and stress with positive emotions such as gratitude. The purpose of this research is to determine the effect of gratitude on anxiety and stress in students. Quantitative methods were used in this research by taking samples through r simple random sampling. The sample in this study was students in the city of Samarinda, with data collected using the gratitude questionnaire (GQ-6) and Depression, Anxiety and stress Scale (DASS-21). This research uses multiple linear regression statistical analysis. The results of this study found that there was a significant influence regarding gratitude on anxiety and stress among students in the city of Samarinda. With a high sense of gratitude, students can reduce anxiety and stress so that students' lives become calmer, more prosperous and happier